Interest of exome sequencing trio‐like strategy based on pooled parental DNA for diagnosis and translational research in rare diseases. Issue 12 (30th October 2021) - Tran Mau‐Them, Frederic; Duffourd, Yannis; Vitobello, Antonio; Bruel, Ange‐Line; Denommé‐Pichon, Anne‐Sophie; Nambot, Sophie; Delanne, Julian; Moutton, Sebastien; Sorlin, Arthur; ,; Couturier, Victor; Bourgeois, Valentin; et al.
Abstract: Background: Exome sequencing (ES) has become the most powerful and cost‐effective molecular tool for deciphering rare diseases with a diagnostic yield approaching 30%–40% in solo‐ES and 50% in trio‐ES. We applied an innovative parental DNA pooling method to reduce the parental sequencing cost while maintaining the diagnostic yield of trio‐ES. Methods: We pooled six (Agilent‐CRE‐v2–100X) or five parental DNA (TWIST‐HCE–70X) aiming to detect allelic balance around 8–10% for heterozygous status. The strategies were applied as second‐tier (74 individuals after negative solo‐ES) and first‐tier approaches (324 individuals without previous ES). Results: The allelic balance of parental‐pool variants was around 8.97%. Sanger sequencing uncovered false positives in 1.5% of sporadic variants. In the second‐tier approach, we evaluated than two thirds of the Sanger validations performed after solo‐ES (41/59–69%) would have been saved if the parental‐pool segregations had been available from the start. The parental‐pool strategy identified a causative diagnosis in 18/74 individuals (24%) in the second‐tier and in 116/324 individuals (36%) in the first‐tier approaches, including 19 genes newly associated with human disorders. Conclusions: Parental‐pooling is an efficient alternative to trio‐ES. It provides rapid segregation and extension to translational research while reducing the cost of parental and Sanger sequencing. Abstract : We applied an innovative parental DNA pooling method to reduce the parental sequencing cost while maintaining the diagnostic yield of trio‐ES. Parental‐pooling is an efficient alternative to trio‐ES. It provides rapid segregation and extension to translational research while reducing the cost of parental and Sanger sequencing.